"Rimi Bowl" and the Quest for Authenticity: Fan Autonomy and Commodification in Norwegian Football. (April 2015) - Hognestad, Hans Kristian
Football in Norway is facing similar challenges as other European leagues regarding dwindling crowds and financial instability, in the wake of the neoliberal boom from the 1990s and well into the new millennium. The years between 1990 and 2008 saw a doubling of average crowds for top-level games. Yet since 2008, there has been a steady decline, even for the biggest clubs. Clubs and the Norwegian Football Association (FA). respond differently to these trends, and a variety of initiatives have increased the level of oppositional activism among groups of dedicated fans. A fresh example of this was when the biggest club in Oslo, Vålerenga, decided to let their main sponsor, the supermarket chain Rimi, use a game to celebrate the opening of their 300th shop. With clear references to the razzamatazz of the Super Bowl, the sponsor named the event "Rimi Bowl" and, in an attempt to attract new spectators, sold tickets in their shops for just NOK50 (£5). However, with bands and various artists performing before the game and during the interval, a lot of fans felt the "event" was advertised more as a hyper commercial show than a football game. A storm of protests was aired in newspapers and in Internet forums among fans of Vålerenga—followed by individuals and groups who supported the initiative and made counter protests. This article will provide a discussion of how commercialization is contested among different fan groups in Norway.